Add Sugar to Chitosan: Mucoadhesion and In Vitro Intestinal Permeability of Mannosylated Chitosan Nanocarriers - Sadaf Ejaz; Bridget Hogg; Delyan R. Hristov; David J. Brayden; Muhammad Imran; Sourav Bhattacharjee (MDPI AG, 2022)
Crosslinked chitosan nanocarriers (140-160 nm) entrapping coumarin-6 (λex/em = 455/508 nm) with or without surface mannosylation were synthesized and assessed for cytotoxicity, adherence and cellular uptake in Caco-2 cells, flux across Caco-2 monolayers, and mucoadhesion to porcine mucin. Mannosylated and non-mannosylated nanocarriers demonstrated biocompatibility with slow release of coumarin-6 at pH 6.8 and 7.4 over 24 h. Adherence of the non-mannosylated nanocarriers (50 and 150 µg/mL) to Caco-2 cells was ~10% over 24 h, whereas cellular uptake of 25-30% was noted at 4 h. The mannosylated nanocarriers showed a similar adherence to non-mannosylated nanocarriers after 24 h, but a lower cellular uptake (~20%) at 1 h, comparable uptake at 4 h, and a higher uptake (~25-30%) at 24 h. Overall, the nanocarriers did not affect the integrity of Caco-2 monolayers. Mannosylated nanocarriers elicited higher Papp of 1.6 × 10−6 cm/s (50 µg/mL) and 1.2 × 10−6 (150 µg/mL) than the non-mannosylated ones: 9.8 × 10−7 cm/s (50 µg/mL) and 1.0 × 10−6 (150 µg/mL) after 2 h. Non-mannosylated chitosan nanocarriers elicited enhanced adhesion to porcine gut mucin via mucin-filled microchannels due to higher cationic charge density. These results underpin the importance of surface chemistry in the biological interactions of nanocarriers, while highlighting the role of surface hydrophilicity in mucopermeation due to mannosylation.